Development and Characterization of New Monoclonal Antibodies against Human Recombinant CA XII. (20th May 2014) - Dekaminaviciute, Dovile; Lasickiene, Rita; Parkkila, Seppo; Jogaite, Vaida; Matuliene, Jurgita; Matulis, Daumantas; Zvirbliene, Aurelija
Abstract : Carbonic anhydrases (CAs) are enzymes that catalyse the reversible hydration of CO2 to bicarbonate. CA XII is considered a potential biomarker of tumor cells and a promising target for specific therapies. The aim of the current study was to develop new monoclonal antibodies (MAbs) against human recombinant CA XII and evaluate their diagnostic potential. An extracellular catalytic domain of human CA XII was expressed in E. coli and used as an immunogen. Seven stable hybridoma cell lines producing high-affinity IgG antibodies against human CA XII were generated. The majority of MAbs were highly specific to CA XII and did not cross-react with human recombinant CA I, CA II, CA VII, and CA XIII. In order to demonstrate the diagnostic value of the MAbs, they were employed for the immunohistochemistry analysis of CA XII expression in tissues. Two MAbs (15A4 and 4A6) demonstrated a strong and specific immunostaining of CA XII in human tissue specimens. Flow cytometry analysis of 5 human tumor cell lines with the MAb 15A4 revealed its immunoreactivity with cellular CA XII. In conclusion, the MAbs raised against recombinant catalytic domain of CA XII recognize cellular CA XII and represent a promising diagnostic tool for the immunodetection of CA XII-expressing cells.